Nitrogen‐Enriched Mesoporous Carbon Spheres as Efficient Anode Material for Long‐Cycle Li/Na‐Ion Batteries. Issue 8 (9th March 2022) - Ali, Shamshad; Waqas, Muhammad; Thaheem, Imdadullah; Hussain, Ayaz; Soomro, Afaque Manzoor; Bhutto, Zuhaibuddin; Muhammad, Wazir; Shah, Syed Ali Raza; Shah, Jalal
Abstract : Nitrogen doping with carbon material substantially enhances the electrochemical properties in lithium and sodium batteries. However, direct treating at high temperature fails to create high nitrogen content, thus limiting the morphological as well as electrochemical performances. Herein, a hydrophilic material xanthan and acid‐treated melamine are doped by a dual process of hydrothermal and carbonization, enabling high nitrogen content (28%) carbon spheres. The highly defected nanosphere structures ( I D / I G = 1.14) enable the high specific surface area of 388 m 2 g −1, which facilitates a large number of lithium/sodium ions and gives rise to remarkable electrochemical performances. When applied as an anode, the nitrogen‐doped porous sphere xanthan (NPS‐XAN) delivers a superior discharge capacity of 390 mAh g −1 after 1000 cycles at a current density of 1 A g −1 for lithium anode and maintains a discharge capacity of 262 mAh g −1 after 2800 cycles at 1 A g −1 for sodium anode. This work signifies superior capacity anodes for Li/Na‐ion batteries and contributes to the long‐life cycling energy application. Abstract : The nitrogen‐doped porous sphere xanthan (NPS‐XAN) anode is prepared for lithium/sodium‐ion batteries. The high nitrogen content of (28%) carbon spheres enables high defect nanosphere structures ( I D / I G = 1.14) and high specific surface area of (388 m 2 g −1 ); as a result, superior discharge capacities are achieved for lithium/sodium batteries.